Dengue diagnosis and impact on clinical management: A literature review. - Solenne Robert; Potiandi Serge Diagbouga; Arthur Diakourga Djibougou; Danielle Guy; Robert Bagnall; Fanette Ravel (PLoS Neglected Tropical Diseases, 2025)
Background Dengue is a re-emerging infectious disease that poses substantial challenges to healthcare systems in endemic regions, such as West Africa. Owing to its nonspecific and overlapping clinical symptoms - including fever, rash, headache, joint pains, nausea, vomiting - many cases go unrecognized or are misdiagnosed. Consequently, patients are often inappropriately treated with antimalarial or antibiotic therapies. Such mismanagement not only affects patient outcomes but also contributes to the development of antimicrobial and antimalarial drug resistance within these populations. This literature review aimed to describe the patterns and impact of dengue diagnosis in West Africa. Methods A comprehensive electronic database search of MEDLINE and Embase was conducted using keywords related to dengue, chikungunya, acute febrile illness, diagnostic strategies, and clinical management. Additional manual searches was performed through Google Scholar and relevant conference proceedings. Eligible studies included observational, real-world evidence, or interventional research conducted in West Africa involving adult patients diagnosed with dengue or chikungunya. Inclusion criteria required studies to report on diagnostic approaches and/or clinical management strategies. Due to the limited availability of data on chikungunya, this review focused exclusively on dengue. Results Ten studies from Burkina Faso, Ivory Coast, Senegal, and Nigeria were included in this review. Rapid serologic testing (DENGUE NS1, IgG, IgM) was the most frequently used diagnostic tools, used in 60% of the studies. Clinical management of dengue primarily involved the administration of antipyretics, fluid therapy, and blood transfusions when necessary. In five studies, antimalarial treatments were systematically prescribed despite negative malaria results. Additionally, two studies reported the use of antibiotics without confirmed bacterial infection or supporting biological diagnosis, indicating inappropriate antibiotic use. Conclusions Evidence on dengue diagnosis and related clinical management in West Africa remains limited. The available data indicate a widespread underuse of diagnosis tools and frequent misuse of antimalarial and antibiotic therapies in the management of dengue. Future studies should prioritize evaluating the impact of accurate differential diagnosis between dengue and malaria on patient care, particularly regarding the inappropriate use of antibiotics and antimalarials. Moreover, integrating routine diagnostic testing into standard clinical practice, as recommended by health authorities, could significantly improve current management. This would enable clinicians to more accurately diagnose dengue, malaria, other febrile illnesses, and potential co-infections, ultimately reducing the misuse of antimicrobial treatments.